(untitled) (Research, Society and Development, 2023)
War conflicts for several decades have produced forced migration, and today these displacements are more visible worldwide due to the great access to information – becoming a serious problem in humanitarian aid and impacting on mental health, quality of life, increased violence and situations of vulnerability as well as social isolation resulting from prejudice. The inclusion of these people in the health system becomes a major challenge for Brazilian authorities, leaving them at the mercy of precarious housing, food, education and health conditions. Therefore, the present work aims to analyze the panorama of refugees’ access to healthcare in Brazil. We chose to carry out an integrative literature review, based on a systematic search for scientific articles indexed in the following databases: Scientific Electronic Library Online (SciELO) data; Latin American and Caribbean Literature in Health Sciences (LILACS); U.S. National Library of Medicine (PubMed); and Medical Literature Analysis and Retrieval System Online (MEDLINE). It was noted that there is great difficulty in accessing the Unified Health System due to problems related to language, culture, prejudices on the part of workers and little allocation of financial resources to the cause, generating more inequality and difficulty in accessing health services. Thus, the lack of access of refugees to health services goes against human rights and Brazilian laws and principles, and it is extremely important that the Brazilian federal government, states and municipalities find ways to repair this conflict and improve the quality of life of these people in a state of physical and mental suffering.